Islam Posmodernisme - Abdurrahman, Muslim (UIN Maulana Malik Ibrahim Malang, 2007)
In this modem era, Islam, in fact, has a significant influence in politics and culture. Western people regard this as a symptom of the emergence of Islamic fundamentalism. It is a reaction of Islam to modernism and capitalism. Even though the term is not purely from Islamic terminology, for Western academicians it virtually represents Islam. Even, they relate it to terrorist movements. It takes us back to remarkable phenomena of secularism embedding that happened in Europe two decades ago. Modernism and capitalism have effects not only on Islam but also on other non-Islamic countries. Therefore, it is not surprising if then in this era of global capitalism Western academicians try to eliminate the thesis of secularism in their fundamentalism project. In the third millennium, after the fall of communism in Russia and Western Europe, Western is interested in studying Islam, if truth to be told, it is more intense. They are afraid of the influence of Islam for which the fundamentalists struggle to realize Islam as the grand narrative, a blue print of universal ideology that often impedes Western hegemony with its liberal democracy. Pada zaman modern ini, nyatanya Islam memiliki pengaruh signifikan dalam Politik dan budaya. Orang Barat menganggap ini sebagai pertanda kemunculan fundamentalis Islam. Hal itu adalah reaksi Islam terhadap modernisme dan kapitalisme. Meskipun begitu, istilah tersebut tidak berasal dari istilah Islam, hanya saja menurut akademis Barat, istilah tersebut merepresentasikan Islam secara virtual. Bahkan, mereka mengaitkannya dengan gerakan teroris. Hal ini membawa kita kembali pada fenomena dahsyat sekularisme yang terjadi di Eropa dua dekade lalu. Modernisme dan kapitalisme berefek tak hanya pada Islam tapi juga pada negara-negara non-Islam. Maka dari itum tidak mengejutkan jika dalam era kapitalisme global, akademisi Barat mencoba menyingkirkan hipotesis sekularisme dalam proyek fundamentalismenya. Pada milenium ketiga, pasca runtuhnya komunisme di Rusia dan Eropa Barat, negara Barat mulai tertarik mempelajari Islam. Karena jika kebenaran diungkapkan, maka akan lebih hebat. Mereka takut akan pengaruh Islam bagi para fundamentalis yang berjuang untuk menyadarkan Islam sebagai narasi besar, sebuah blue print ideologi universal yang sering mengahalangi hegemoni Barat dengan demokrasi liberalnya.